Measurement of the [Formula: see text] production cross section in the tau + jets channel using the ATLAS detector - Aad, G. (Eur Phys J C Part Fields, 2013)
A measurement of the top quark pair production cross section in the final state with a hadronically decaying tau lepton and jets is presented. The analysis is based on proton–proton collision data recorded by the ATLAS experiment at the LHC, with a centre-of-mass energy of 7 TeV. The data sample corresponds to an integrated luminosity of 1.67 fb(−1). The cross section is measured to be [Formula: see text] and is in agreement with other measurements and with the Standard Model prediction.